Studying a droplet impaction on a vibrating porous medium - Eslam Ezzatneshan; Reza Sadraei; Reza Goharimehr (Engineering Applications of Computational Fluid Mechanics)
This study investigates the influence of vibration on droplet dynamics when a droplet impacts a three-dimensional (3D) structured porous medium, focusing on intrinsic properties such as porosity and wettability, along with the effect of vibration phase angle. Using an Allen-Cahn equation-based lattice Boltzmann method (A-C LBM), the research analyzes multiphase flow dynamics. The results compare droplet spreading and penetration on vibrating versus non-vibrating porous media. Without vibration, droplets get trapped within the pores, reaching equilibrium due to adhesive, viscous, and capillary forces. However, sufficient vibrational forces can overcome surface adhesion, allowing droplets to pass through the porous medium. This phenomenon is influenced by the droplet's contact angle and initial impact inertia. The study finds that hydrophobic surfaces, characterised by higher contact angles, significantly reduce liquid infiltration into the medium under both vibrational and non-vibrational conditions. This reduction is due to dominant surface tension and repellent forces, which, in combination with vibrational forces, minimise droplet spreading and penetration, even in highly porous media. Conversely, on hydrophilic surfaces, adhesive and capillary forces enhance the droplet's inertia, causing sudden penetration into the porous medium. Further, the study reveals that the phase angle of vibration critically affects the droplet's behaviour. With sinusoidal vibration, lower phase angles cause the porous medium to move in the opposite direction to the droplet, enhancing the synergy between vibration and inertia forces, leading to rapid infiltration. Higher phase angles, aligning the medium's movement with the droplet's impact path, result in reduced infiltration. Overall, this research provides crucial insights into how porosity, wettability, and vibration phase angle collectively influence droplet dynamics on structured porous media, offering valuable implications for applications involving fluid transport and filtration in porous structures.